Space Manifold Dynamics Novel Spaceways for Science and Exploration - Perozzi, Ettore; Ferraz-Mello, Sylvio; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
This book presents an overview of the outcomes resulting from applying the dynamical systems approach to space mission design, a topic referred to as "Space Manifold Dynamics" (SMD). It is a natural follow-on to the international workshop "Novel Spaceways for Scientific and Exploration Missions," which was held in October 2007 at the Telespazio Fucino Space Centre (Italy) under the auspices of the Space OPS Academy. The benefits and drawbacks of using the Lagrangian points and the associated trajectories for present and future space missions are discussed. The related methods and algorithms are also described in detail. Each topic is presented in articles that were written as far as possible to be self consistent; the use of introductory sections and of extended explanations is included in order to address the different communities potentially interested in SMD: space science, the aerospace industry, manned and unmanned exploration, celestial mechanics, and flight dynamics.
Invariant Manifolds, Lagrangian Trajectories and Space Mission Design -- Chaos and Diffusion in Dynamical Systems Through Stable-Unstable Manifolds -- Regular and Chaotic Dynamics of Periodic and Quasi-Periodic Motions -- Survey of Recent Results on Weak Stability Boundaries and Applications -- On the Accessibility of the Moon -- Optimal Low-Thrust Trajectories to the Interior Earth-Moon Lagrange Point -- On the Use of the Earth-Moon Lagrangian Point L 1 for Supporting the Manned Lunar Exploration -- Manifolds and Radiation Protection -- Three-Body Invariant Manifold Transition with Electric Propulsion -- From Sputnik to the Moon: Astrophysics and Cosmology from Space -- Space Exploration: How Science and Economy may Work Together.
Keywords: Physics; Planetology; Astrophysics; Astronautics; Physics; Extraterrestrial Physics, Space Sciences; Aerospace Technology and Astronautics; Planetology